2002
DOI: 10.1016/s0960-9822(02)01391-x
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Specific Targeting of H3K9 Methylation Is Sufficient for Initiating Repression In Vivo

Abstract: Covalent modifications of chromatin have emerged as key determinants of the genome's transcriptional competence. Histone H3 lysine 9 (H3K9) methylation is an epigenetic signal that is recognized by HP1 and correlates with gene silencing in a variety of organisms. Discovery of the enzymes that catalyze H3K9 methylation has identified a second gene-specific function for this modification in transcriptional repression. Whether H3K9 methylation is causative in the initiation and establishment of gene repression or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
193
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(200 citation statements)
references
References 20 publications
5
193
0
2
Order By: Relevance
“…Here, we added that also on irrelevant genes no enrichment of the fusion protein could be detected and interestingly genome-wide data showed that the Her2/neu ZFP is preferentially bound to Her2/neu gene. The domains of G9a and SUV39-H1 used in our ZFP fusion complexes have been previously reported to result in H3K9 methylation of the promoter of VEGF-A gene and in downregulation of this gene (30). We showed here that the approach is also suitable for downregulation of an overexpressed oncogene.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Here, we added that also on irrelevant genes no enrichment of the fusion protein could be detected and interestingly genome-wide data showed that the Her2/neu ZFP is preferentially bound to Her2/neu gene. The domains of G9a and SUV39-H1 used in our ZFP fusion complexes have been previously reported to result in H3K9 methylation of the promoter of VEGF-A gene and in downregulation of this gene (30). We showed here that the approach is also suitable for downregulation of an overexpressed oncogene.…”
Section: Discussionmentioning
confidence: 61%
“…In this study, catalytic domains of 2 histone methyltransferases were cloned as reported previously (30). For G9a, the N-terminal domain (amino acid 1-829) was not included (excluding most of the ankyrin repeats); for SUV39-H1, the C-terminal region encoding amino acids 76-412 was amplified, lacking the N-terminal HP1 interaction domain.…”
Section: Constructs and Retroviral Transductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others favour the view that histone deacetylation, histone methylation, DNA methylation and the production of small RNAs, all work together in various orders to bring about an efficient silent state (Grewal and Moazed, 2003). Remarkably, these epigenetic silencing mechanisms can be targeted to ectopic genes, thereby marking chromatin in such a way that this silencing state is inherited over many cell generations (Snowden et al, 2002;Ayyanathan et al, 2003).…”
mentioning
confidence: 97%